Analisis Kemampuan Literasi Matematis Peserta Didik Sekolah Menengah dalam Menyelesaikan Soal PISA Konten Quantity Ditinjau dari Math Anxiety - Sausan, Tamara; Wibowo, Muhammad Umar (UIN Sunan Gunung Djati Bandung, 2024)
A person's mathematical literacy ability is influenced by various factors, one of which is math anxiety. Math anxiety causes anxiety, fear, and dislike of mathematics, which affects the ability to solve mathematical literacy problems. This research is a descriptive qualitative research that uses a case study approach to 31 students at SMP UPI Laboratorium UPI Cibiru and selected 3 students who represent each level of low, medium, and high mathematical anxiety. The research instruments used were questionnaires, PISA tests on quantity content levels 1 to 3, and interviews. Subjects with low math anxiety solved the quantity content PISA questions up to level 3 and achieved the mathematical literacy indicators of applying and interpreting. Subjects with moderate math anxiety level could solve PISA questions on quantity content up to level 3 with the achievement of formulating, applying, and interpreting indicators. Subjects with high math anxiety level only achieved the applying indicator on level 2 questions. Subjects who have the best literacy skills are subjects with moderate math anxiety, followed by subjects with low and high math anxiety. So, students with high math anxiety may have low math literacy skills and vice versa. Future research can conduct research with the next level of PISA questions with quantity content or different content.